DIPLOMASI EKONOMI INDONESIA TERHADAP KOREA SELATAN DALAM UPAYA MENINGKATKAN EKSPOR UDANG KE KOREA SELATAN PERIODE 2014-2019 - Muhamad Rizky Aprizon (2020)
This study describes the economic diplomacy conducted by Indonesia towards South Korea in an effort to increase shrimp exports in 2014-2019. South Korea is a developed country in East Asia that has a high level of seafood consumption, especially consumption of shrimp-based seafood. But South Korea's fisheries production is not sufficient to meet the needs of domestic seafood consumption of its citizens, so 70% of seafood must be imported from abroad. This condition is an opportunity for Indonesia as the number four shrimp exporter in the world to increase shrimp exports to South Korea through economic diplomacy such as the Indonesian Trade Expo which is held annually. This study uses the basic theoretical framework of Comparative Advantage (Comparative Advantage Theory) and economic diplomacy theory. This study uses qualitative research methods as well as references taken from news websites, ministry pages, journals, and books. Through a series of economic diplomacy such as the Trade Expo Indonesia can promote superior products owned by Indonesia, especially Indonesia's leading commodities such as shrimp to South Korean importers. In addition, through trade representative institutions in South Korea namely ITPC Busan, Indonesia actively participates in trade exhibitions such as the Busan International Seafood & Fisheries Expo (BISFE) and the Seoul International Seafood Show. Following the trade exhibition in South Korea is Indonesia's effort to carry out the function of economic diplomacy through promotion and negotiation. Indonesian shrimp has been proven as a commodity that is free of EMS disease and can meet the import standards of developed countries.